2011
DOI: 10.3920/bm2011.0032
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive post-market review of studies on a probiotic product containing Lactobacillus helveticus R0052 and Lactobacillus rhamnosus R0011

Abstract: The probiotic preparation Lacidofil® has been commercially available in Europe, Asia and North America since 1995. This product is a combination of two strains, Lactobacillus helveticus R0052 and Lactobacillus rhamnosus R0011. The strains have been evaluated for safety, identity and mechanisms of probiotic action in vitro, in animal models and human clinical trials. The strains adhered to human epithelial cells, helped to maintain the barrier function and blocked the adhesion of a number of pathogens, allowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 64 publications
2
44
0
3
Order By: Relevance
“…The level of therapeutic efficacy of heat-treated and lyophilized L. acidophilus LB cells and culture medium against established infectious acute watery diarrhoea (MD −21.6 hours, 95% CI −26.5 to −16.6) [Szajewska et al 2014a] is close to the level found by Allen and colleagues [Allen et al 2010] in their Cochrane analysis of 63 RCTs L. rhamnosus R0011 (CNCM I-1720) and L. helveticus R0052 (CNCM I-1722) strains isolated from dairy [Foster et al 2011], there was only one RCT (unknown aetiology; MD −23.8 hours, 95% CI −60.0 to −9.6) [Szajewska et al 2014a].…”
Section: Comparison With Different Marketed Probiotic Lactobacillus Ssupporting
confidence: 62%
“…The level of therapeutic efficacy of heat-treated and lyophilized L. acidophilus LB cells and culture medium against established infectious acute watery diarrhoea (MD −21.6 hours, 95% CI −26.5 to −16.6) [Szajewska et al 2014a] is close to the level found by Allen and colleagues [Allen et al 2010] in their Cochrane analysis of 63 RCTs L. rhamnosus R0011 (CNCM I-1720) and L. helveticus R0052 (CNCM I-1722) strains isolated from dairy [Foster et al 2011], there was only one RCT (unknown aetiology; MD −23.8 hours, 95% CI −60.0 to −9.6) [Szajewska et al 2014a].…”
Section: Comparison With Different Marketed Probiotic Lactobacillus Ssupporting
confidence: 62%
“…The probiotic strains were chosen for their commercial use in fermented food products such as cheese and yogurt, L. helveticus RO052 and L. rhamnosus RO011 originating from dairy products (Hagen et al, 2010; Foster et al, 2011). Both strains are resistant to acidic pH levels (Dimitrov et al, 2005; Succi et al, 2005) which are known to negatively affect probiotic viability, especially during dairy product storage (Champagne et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity studies for these two strains have been completed and no toxicity was observed (Foster et al, 2011). B. animalis subsp.…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that there is insufficient evidence to recommend L. acidophilus strain LB for treating diarrhea in children (24). Some studies also examined the effect of AGE treatment using other Lactobacillus species, some Bifidobacterium species, Streptococcus thermophilus, and other probiotics (25)(26)(27)(28). However, there is not enough evidence to recommend these probiotics for routine use in AGE (6).…”
Section: Placebo Groupmentioning
confidence: 99%